2006
DOI: 10.1017/s0376892906003134
|View full text |Cite
|
Sign up to set email alerts
|

A re-emerging Atlantic forest? Urbanization, industrialization and the forest transition in Santa Catarina, southern Brazil

Abstract: During the second half of the twentieth century, southern Brazil underwent rapid industrialization and urbanization. In earlier historical periods in Europe and North America, these trends have contributed to a forest transition in which deforestation gives way to forestation. In a developing country, like Brazil, with a more skewed income distribution and a larger rural underclass, industrialization and urbanization may not give rise to a forest transition. These competing theoretical expectations were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
1
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 16 publications
8
64
1
11
Order By: Relevance
“…Although some studies suggest that the forest cover has stabilized and could even be increasing (Kronka et al, 2005), our results and those from other sites in the Atlantic Rainforest (Baptista and Rudel, 2006) and from other tropical regions (Neeff et al, 2006) suggest that stable or increasing forest cover is a result of the replacement of older forests by younger forests. Moreover, from 2000 to 2005 more than 170,000 ha of Atlantic Rainforest were lost (Fundação SOS Mata Atlântica and INPE, 2008).…”
Section: Landscape Dynamics and Proximate Causescontrasting
confidence: 69%
“…Although some studies suggest that the forest cover has stabilized and could even be increasing (Kronka et al, 2005), our results and those from other sites in the Atlantic Rainforest (Baptista and Rudel, 2006) and from other tropical regions (Neeff et al, 2006) suggest that stable or increasing forest cover is a result of the replacement of older forests by younger forests. Moreover, from 2000 to 2005 more than 170,000 ha of Atlantic Rainforest were lost (Fundação SOS Mata Atlântica and INPE, 2008).…”
Section: Landscape Dynamics and Proximate Causescontrasting
confidence: 69%
“…Exploration of changes in rural income over time presented a mixed picture. Some studies have found evidence that rising incomes slowed and reversed the loss of forest cover, as in Vietnam (Muller and Zeller 2003) and China (Gong 2013), but other studies have found that greater income led to greater deforestation in China (Li 2013) or had no effects on trends in forest cover in Brazil (Baptista and Rudel 2006), Panama (Sloan 2008), China (Zhao et al 2011), and Mexico (Vaca 2012). A broader meta-analysis and synthesis of studies of the so-called "Environmental Kuznets Curve for deforestation" found the evidence supporting the theory to be mixed and diminishing over time (Choumert et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…However, the forests reduction process has been decelerated since the end of the last century so that this scenario has changed in some regions with the increase of the secondary forests area (Baptista and Rudel, 2006). This change has occurred in response to the creation of federal environmental laws and the social and economic forces that resulted in rural exodus (Baptista and Rudel, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the forests reduction process has been decelerated since the end of the last century so that this scenario has changed in some regions with the increase of the secondary forests area (Baptista and Rudel, 2006). This change has occurred in response to the creation of federal environmental laws and the social and economic forces that resulted in rural exodus (Baptista and Rudel, 2006). Yet it is observed that the disturbance regime in MOF areas currently shows different characteristics, where the more intense and punctual impacts that used to be frequent have been supplanted by low-level but chronic disturbances, such as cattle presence (Sampaio and Guarino, 2007;Silva et al, 2012) and the exploitation of non-timber resources (Mello and Peroni, 2015).…”
Section: Introductionmentioning
confidence: 99%